2004
DOI: 10.1007/s00232-004-0709-4
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Peptide Channels

Abstract: At least 16 distinct clinical syndromes including Alzheimer's disease (AD), Parkinson's disease (PD), rheumatoid arthritis, type II diabetes mellitus (DM), and spongiform encephelopathies (prion diseases), are characterized by the deposition of amorphous, Congo red-staining deposits known as amyloid. These "misfolded" proteins adopt beta-sheet structures and aggregate spontaneously into similar extended fibrils despite their widely divergent primary sequences. Many, if not all, of these peptides are capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 83 publications
6
144
0
9
Order By: Relevance
“…It is widely accepted that, at least in most cases, cell degeneration in amyloid diseases is mediated by a toxic mechanism involving the interaction of the aggregated species with the plasma membrane of the affected cells (Kagan et al, 2004). Some authors suggest that, by affecting plasma membrane fluidity, cholesterol content affects the incorporation of toxic aggregates into the plasma membrane itself (Arispe and Doh, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that, at least in most cases, cell degeneration in amyloid diseases is mediated by a toxic mechanism involving the interaction of the aggregated species with the plasma membrane of the affected cells (Kagan et al, 2004). Some authors suggest that, by affecting plasma membrane fluidity, cholesterol content affects the incorporation of toxic aggregates into the plasma membrane itself (Arispe and Doh, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Micro-circumstances on the membranes, such as the presence of rafts, may influence this process [56]. These data and other reports culminated in what came to be known as the "channel hypothesis", implicating amyloid peptide channels in the pathogenic ion dysregulation observed in degenerative disease [57,58]. In this respect, A␤ may share this mechanism of toxicity with the similar mechanism underlying the toxicity of various antimicrobial or antifungal peptides, such as alamethicin, gramicidin, magainin 2, and melittin, which also exhibit channel forming ability and cell toxicity [59].…”
Section: Cellular Membrane and A␤ Oligomers Toxicitymentioning
confidence: 92%
“…In particular, it was reported that A␤ can induce a generalized thinning of the phospholipid bilayer, thereby resulting in perturbation of Ca 2+ fluxes [23]. The formation of stable pores and ion channels, usually defined "annular protofibrils", in the cell membrane has also been proposed for amyloid-induced toxicity, in analogy to prokaryotic pore-forming toxins [24][25][26], although more recent data have not supported this hypothesis. Finally, a mechanism of A␤ oligomer interaction with cell membranes involving specific binding to endogenous calcium-permeable channels has also been suggested [18].…”
Section: Introductionmentioning
confidence: 99%